Model of the Influence of Sensory Formal Aesthetics in Encouraging Ecological Behavior Case Study: Sky Garden Mall PVJ, Bandung - Graciela, Cindy Fiolita; Sanjaya, Ridwan; Widjaja, Robert Rianto (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2025)
This research aims to determine the influence of formal sensory aesthetics in encouraging ecological behavior among visitors at PVJ Sky Garden mall, Bandung, in the form of a model. Environmental damage is becoming increasingly uncontrollable due to human behavior that is not environmentally friendly, one of which is in the city of Bandung. Therefore, efforts are needed to encourage the community to adopt ecological behaviors through intensive green roof facilities. In addition to the ecological role of green roofs, aesthetics play an important role in influencing behavior. This occurs through the reciprocal relationship between aesthetics and behavior. The theory of aesthetics and ecological behavior is analyzed into a proposition model, then used as the basis for the research framework and tested on mall visitors. Qualitative research method with a case study approach by Robert K. Yin, through direct observation to observe aesthetics and behavior, questionnaire surveys on mall visitors and experts, interviews, and expert validation to deepen and develop data on the model. The research findings consist of a sensory formal aesthetic model that can influence the ecological behavior of visitors. The aesthetic aspects, which consist of elements of environmental education, spaces for cultural gatherings, designs resembling the original nature that evoke a sense of leisure, and the selection of local materials, play an important role in influencing the ecological behavior of visitors to the PVJ Sky Garden Mall.